Artificial Engineered Natural Killer Cells Combined with Antiheat Endurance as a Powerful Strategy for Enhancing Photothermal‐Immunotherapy Efficiency of Solid Tumors. Issue 42 (29th August 2019) - Zhang, Da; Zheng, Youshi; Lin, Ziguo; Lan, Shanyou; Zhang, Xiaolong; Zheng, Aixian; Li, Juan; Liu, Gang; Yang, Huanghao; Liu, Xiaolong; Liu, Jingfeng
Abstract: Although photothermal therapy (PTT) is preclinically applied in solid tumor treatment, incomplete tumor removal of PTT and heat endurance of tumor cells induces significant tumor relapse after treatment, therefore lowering the therapeutic efficiency of PTT. Herein, a programmable therapeutic strategy that integrates photothermal therapeutic agents (PTAs), DNAzymes, and artificial engineered natural killer (A‐NK) cells for immunotherapy of hepatocellular carcinoma (HCC) is designed. The novel PTAs, termed as Mn‐CONASHs, with 2D structure are synthesized by the coordination of tetrahydroxyanthraquinone and Mn 2+ ions. By further adsorbing polyetherimide/DNAzymes on the surface, the DNAzymes@Mn‐CONASHs exhibit excellent light‐to‐heat conversion ability, tumor microenvironment enhanced T 1 ‐MRI guiding ability, and antiheat endurance ability. Furthermore, the artificial engineered NK cells with HCC specific targeting TLS11a‐aptamer decoration are constructed for specifically eliminating any possible residual tumor cells after PTT, to systematically enhance the therapeutic efficacy of PTT and avoid tumor relapse. Taken together, the potential of A‐NK cells combined with antiheat endurance as a powerful strategy for immuno‐enhancing photothermal therapy efficiency of solid tumors is highlighted, and the current strategy might provide promising prospects for cancer therapy. Abstract : Herein, a programmable antitumor strategy that combines artificial engineered natural killer cells with the antiheat endurance of DNAzyme as a powerful strategy for immuno‐improving the therapeutic efficiency of photothermal therapy is reported.